Community dimensions and emotions in the era of COVID‐19. (15th August 2021) - Marzana, Daniela; Novara, Cinzia; De Piccoli, Norma; Cardinali, Paola; Migliorini, Laura; Di Napoli, Immacolata; Guidi, Elisa; Fedi, Angela; Rollero, Chiara; Agueli, Barbara; Esposito, Ciro; Marta, Elena; et al.
Abstract: Following an ecological perspective, reactions to a disaster—such as the COVID‐19 pandemic—should be analysed in the interdependence between individual and community dimensions. The present study aims to analyse individual emotional dimensions (anxiety, joy, fear or depressive feelings) and their community dimensions (connectedness, emotional sharing and solidarity) with a longitudinal approach among university students from Italian universities. Participants were 746 university students at t1 (during the lockdown) and 361 at t2 (after the lockdown) recruited in six Italian universities from different areas of Italy. Comparing emotional dimensions in the two times, t2 is characterized by a generalized ambiguity: both happiness or joy because of the end of limitations and a kind of 'post‐lockdown anxiety' because of a sense of individual inadequacy in facing the return to normality, conducting daily activities and attending community spaces. Data confirms that after the so‐called 'honeymoon phase' in community dimensions (first phase of t1 time), a sort of 'depressive reaction' arises at t2: Italian university students seem more aware of the need for individual and social responsibility and that many events are not under their personal control. The reconstruction phase and exit from the emergency are perceived as necessary but also as a difficult and risky period. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement .